2002
DOI: 10.4049/jimmunol.168.10.4907
|View full text |Cite
|
Sign up to set email alerts
|

IFN-αβ Promote Priming of Antigen-Specific CD8+ and CD4+ T Lymphocytes by Immunostimulatory DNA-Based Vaccines

Abstract: Immunostimulatory sequence (ISS) DNA containing unmethylated CpG dinucleotides stimulate NK and APC to secrete proinflammatory cytokines, including IFN-αβ and -γ, TNF-α, and IL-6 and -12, and to express costimulatory surface molecules such as CD40, B7-1, and B7-2. Although ISS DNA has little direct effect on T cells by these criteria, immunization of wild-type mice with ISS DNA and OVA results in Ag-specific CTL and Th1-type T helper activity. This investigation examines the mechanisms by which ISS DNA primes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
83
1

Year Published

2004
2004
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(89 citation statements)
references
References 46 publications
5
83
1
Order By: Relevance
“…7,8 Recent studies demonstrated that IFN-a promotes crosspriming by increasing the expression of Transporters associated with Antigen Processing (TAP)-1 in DCs. 9 In addition, a critical role of type I IFNs in crosspriming of antigen-specific CTLs was directly demonstrated using IFN-a/b receptor-deficient mice. 8 Type I IFNs also directly inhibit proliferation of neoplastic cells through various mechanisms including induction of apoptotic cell death.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Recent studies demonstrated that IFN-a promotes crosspriming by increasing the expression of Transporters associated with Antigen Processing (TAP)-1 in DCs. 9 In addition, a critical role of type I IFNs in crosspriming of antigen-specific CTLs was directly demonstrated using IFN-a/b receptor-deficient mice. 8 Type I IFNs also directly inhibit proliferation of neoplastic cells through various mechanisms including induction of apoptotic cell death.…”
Section: Introductionmentioning
confidence: 99%
“…Several recent reports indicate that the ability to cross-prime CD8 ϩ T cell responses is linked to induction of type I IFN production (48,55,56). Therefore, to determine whether a similar association was true with LANAC-based vaccines, we examined the ability of different liposome-TLR agonist complexes to induce production of IFN-␣ in vivo.…”
Section: Adjuvants Prepared With Tlr9 or Tlr3 Agonists Effectively Crmentioning
confidence: 99%
“…In vitro stimulation of BM-derived DC from wt mice with CpG induced increased surface expression of CD40, CD86, and MHC class I. In contrast, only a subpopulation of BM-derived DC derived from IFN-a/bR À/À mice was capable of upregulating CD40 and CD80 in response to CpG [25]. Other in vitro data show that IFN-a/b promotes the upregulation of the costimulatory molecule CD86 [23].…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, the ability of DC to crosspresent exogenous model antigens such as OVA in the presence of TLR ligands to CD8 1 T cells has been shown to depend on IFN-a/b receptor (IFN-a/bR) signaling. Thus, both MyD88 as well as type I IFN signaling has been shown to be important for the crosspresentation of exogenous model antigens [25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation